(untitled) (Ukrainian Journal of Ophthalmology, 2025)
We report a rare case of penetrating corneal and lens injury with a pars plana foreign body in a teenager and a technique for removing such an intraocular foreign body (IOFB) during complex reconstructive surgery. A 16-year boy was admitted urgently to the Pediatric Ophthalmology Department with complaints of decreased vision in his right eye. He had received a mowing-related injury to the eye three days before presentation. Urgent surgical intervention included initial surgical treatment of the wound, phacoaspiration of traumatic cataract with anterior vitrectomy and endocapsular implantation of a +23.0 D Acrysof SN60WF intraocular lens (IOL), and removal of IOFB from the pars plana. We used wide-spatula scleral compression at the ciliary body not only for visualizing and removing the IOFB, but also for assessing the status of the surrounding tissue (the presence or absence of mild suppurative lesions). The IOFB was removed anteriorly (via cataract incision and anterior and posterior capsulorhexes) with a magnet under direct intraoperative microscopic control. The preservation of residual capsular fornices enabled us to perform primary endocapsular IOL implantation immediately. Therefore, we managed to perform a complete rehabilitation of the injured teenager (IOFB and traumatic cataract removal and endocapsular IOL implantation) using one limbal incision in a single surgery.